Analysis of Association Between Basic and Clinicopathological Characteristics of Papillary Thyroid Carcinoma Patients with BRAF Mutation - Akhter, Papia; Begum, Fatima; Ferdous, Jasmin (Bangladesh Journal of Nuclear Medicine, 2024)
Introduction: The prognosis of papillary thyroid carcinoma (PTC) depends on the patient's age, gender, tumor size, histological findings, extrathyroidal extension, lymph node metastasis, and distant metastasis. Genetic mutations, particularly BRAF (V600E), contribute to metastatic risk factors. Methodology: This prospective cohort study was carried out at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS). A total of 63 patients with PTC after thyroidectomy who were referred to NINMAS for RAIA were included in this study. All the necessary information was collected regarding patients (age, sex) and tumors (size, focality, lymph node involvement, extra-thyroid invasion, distant metastases, staging, and grading). Clinical staging of thyroid cancer was classified according to the tumor-node-metastasis (TNM) classification of the AJCC 8th edition, 2018. All of them were tested for the BRAF (V600E) mutation. Any association between aggressive presentation and BRAF-positive PTC patients was observed. Results: A total of 63 patients, male 25 (39.7%) and female 38 (60.3%), were included in this study. Among them, 23 (36.51%) were BRAF (V600E) positive, and 40 (63.49%) were negative. Extrathyroidal extension, lymphovascular invasion, capsular margin involvement, and larger tumor size were significantly associated with the BRAF mutation. No significant association was found with age, histological type, lymph node involvement, multifocality, tumor staging, or grading. Conclusion: The study suggests that patients with a positive BRAF mutation may benefit from more intensive management and frequent follow-up for aggressive presentation and larger tumor size. Bangladesh J. Nuclear Med. 26(2): 119-123, 2023